2020
DOI: 10.15567/mljekarstvo.2020.0401
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical changes during ripening of cheeses in an animal skin

Abstract: A few types of cheeses ripened in an animal skin sack are produced around the world: Sir iz mišine (Croatia), Sir iz mijeha (Bosnia and Herzegovina and Montenegro), Tulum and Divle Cave (Turkey), Bouhezza (Algeria) and Darfiyeh (Lebanon). Pronounced and piquant taste, flavour and aroma of these cheeses originate from intensive lipolysis and proteolysis as a result of specific anaerobic conditions inside the skin sack, autochthonous microorganisms from raw milk and skin, as well as their manufacturing procedure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…After 187 days, the final average amounts of the short‐chain FFAs (SCFFAs), the medium‐chain FFAs (MCFFAs), and long‐chain FFAs were 8.09%, 14.29%, and 19.60%, respectively. Similar results have been previously reported by Kalit et al., 2020 for Tulum cheese. Lipolysis reactions were progressed very intensely up to day 67 and declined and continued within a very mild slope until the end of the ripening.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…After 187 days, the final average amounts of the short‐chain FFAs (SCFFAs), the medium‐chain FFAs (MCFFAs), and long‐chain FFAs were 8.09%, 14.29%, and 19.60%, respectively. Similar results have been previously reported by Kalit et al., 2020 for Tulum cheese. Lipolysis reactions were progressed very intensely up to day 67 and declined and continued within a very mild slope until the end of the ripening.…”
Section: Resultssupporting
confidence: 93%
“…A few research have previously reported on Kope cheese and its properties including the histamine content (Ehsani et al., 2012), effects of pasteurization and packaging on its physicochemical and sensory properties (Sarbazi et al., 2015), and the influence of ripening time on the structural, rheological, and physicochemical properties of Kope cheese (Hasanzadeh et al., 2018). Cheese ripening is a complex and dynamic biochemical process including primarily lipolysis, proteolysis, lactate metabolism, followed by secondary events, leading to the development of volatile compounds (VCs) and gross composition, which makes an important contribution to flavor perception and texture properties of cheese (Kalit et al., 2020). No scientific information is available about the specific types of free fatty acids (FFAs), organic acids (OAs), and VCs produced during the ripening of Kope cheese.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the ripening period, a series of microbiological and biochemical changes occur, including glycolysis, lipolysis, and proteolysis. Typical properties of cheese such as taste, aroma, and texture are formed by the effect of enzymes obtained from milk, rennet, starter and non-starter bacteria used during that period (van Mastrigt et al, 2018; Chen et al, 2020; Tudor Kalit et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The ripening conditions such as temperature and relative humidity in the ripening chamber and the ripening media (e.g., oil, animal skin, plastic or stone containers, brine, or spices) influence the biochemical processes of glycolysis, proteolysis, and lipolysis, which can consequently lead to the development of specific sensory characteristics of the cheese [15][16][17][18][19]. Thus, cheeses ripened in animal skin (e.g., Sir iz mišine, Tulum, Darfiyeh, and Bouhezza) have a unique and piquant smell, taste, and aroma, which is due to intense lipolysis and proteolysis during ripening conditions in the skin [19][20][21], i.e., lower air permeability of the skin compared to the cheese rind [8], but higher compared to plastic or stone containers, which serve as an alternative ripening medium [22].…”
Section: Introductionmentioning
confidence: 99%